Tomb of Aga Khan I - Mumbai Archive Project Team (Jio Institute, 2024)
Aga Khan I is buried in the central tomb. The tomb of Aga Khan I’s son, Aqa Ali Shah, is located on the right. He was laid to rest after passing away in 1885. Later, his remains were moved to Najaf, near Kufa, on the Euphrates River. On the left side lies the smaller tomb of Pir Abul Hassan Shah, the great-grandson of Aga Khan I, who passed away in 1885 at the age of six months.